An integrated Malaysian 3D cadastre - Hassan, Muhammad Imzan (Penerbit UTM, 2008)
In Malaysia, the cadastre system is controlled by two main ag encies, namely, Department of Surveying and Mapping Malaysia (DSMM) and Land Offices (L.O). The DSMM is responsible for the cadastral spatial information i.e. land parcel boundaries. The mission is to enhance quality in surveying and mapping services along with managing the geospatial data. On the other hand, Lan d Office is responsible for the cadas tral attribute information i.e. legal rights that attached to the cadastral objects or plots . The current system only involves with 2D maps and no effo rt towards 3D registration yet. This pape r discusses 3D cadastre in the aspect of property registration i.e. complex building and overlapping properties on di fferent land use. We also discuss the interoperabil ity of the two systems between the two different ag encies. This 3D cadastre re gistration will serve as a first attempt to develop a mo re complete Integrated Malaysian 3D Cadastre System. A complex system needs a clear a nd concise method to show the representation of data, and here we utilize Unified Modeli ng Language (UML) for the data modeling task as it has been considered better techni que for such real world data modeling like cadastre data compared to the traditional entity relationship approach. Besides 3D regis tration, the paper also discusses 3D mode ling, 3D geo databasing and 3D vi sualization. Malaysia could emba rk on this 3D cadastre system relatively straight forward since it has good 2D cadastre framework. From the research and discussion it can be realized that t he hybrid approach certainly would be a good to start with. This approach means preservation of 2D cadastre and the integration of the registration of the situation in 3D by registering 3D situations integrated and being part of the 2D cadastral geographical dat a set. Nevertheless it is reasonable to believe that there are some irregularities and different inform ation as both systems operates separately. This situation shall trigger a good basis why there is a need for the integration. The challenge is to transform th e proposed model into computer means i.e. logical model. The validation of logical model will be then encoded in the spatial database. Spa tial DBMS is the foundation for both GIS (presenta tion, analysis) and CAD (creating models). It offers spatial data type in its data model structure and also in the query language and it can interact with the spatial DBMS. This paper elaborates on an integration of Oracle Spatial and Autodesk Map 3D for an integrated 3D Cadastre. The 3D Cadastre database development especially on the aspect of 3D objects registration form major contributi ons of the paper towards the developm ent of an integrated 3D Cadastre.